In vivo genetic evidence for suppressing vascular and soft tissue calcification through the reduction of serum phosphate levels, even in the presence of high serum calcium and 1,25-dihydroxyvitamin-D levels - Ohnishi, Mutsuko (2009)
BACKGROUND: Klotho knockout mice (klotho(-/-)) have increased renal expression of sodium/phosphate co-transporters (NaPi2a), associated with severe hyperphosphatemia. Such serum biochemical changes in klotho(-/-)mice lead to extensive soft tissue anomalies and vascular calcification. To determine the significance of increased renal expression of the NaPi2a protein and concomitant hyperphosphatemia and vascular calcification in klotho(-/-)mice, we generated klotho and NaPi2a double knockout (klotho(-/-)/NaPi2a(-/-)) mice. METHODS AND RESULTS: Genetic inactivation of NaPi2a activity from klotho(-/-)mice reversed the severe hyperphosphatemia to mild hypophosphatemia or normophosphatemia. Importantly, despite significantly higher serum calcium and 1,25-dihydroxyvitamin D levels in klotho(-/-)/NaPi2a(-/-) mice, the vascular and soft tissue calcifications were reduced,. Extensive soft tissue anomalies and cardiovascular calcification were consistently noted in klotho(-/-)mice by 6 weeks of age; however, these vascular and soft tissue abnormalities were absent even in 12-week-old double knockout mice. Klotho(-/-)/NaPi2a(-/-) mice also regained body weight and did not develop the generalized tissue atrophy often noted in klotho(-/-)single knockout mice. CONCLUSION: Our in vivo genetic manipulation studies have provided compelling evidence for a pathologic role of increased NaPi2a activities in regulating abnormal mineral ion metabolism and soft tissue anomalies in klotho(-/-) mice. Notably, our results suggest that serum phosphate levels are the important in vivo determinant of calcification, and that lowering serum phosphate levels can reduce or eliminate soft tissue and vascular calcification, even in presence of extremely high serum calcium and 1,25-dihydroxyvitamin D levels. These in vivo observations have significant clinical importance and therapeutic implications for chronic kidney disease patients with cardiovascular calcification.